Hey guys I am struggling with one equation right now, that I need for my bachelor thesis.
Variable x(mth);
Scalar t(w);
binary variable (y(w,mon))
set i,w,mon;
alias (mon,mth);
....
Ver(i,w,mon).. ord(i)*t(w)-1+(M*Y(w,mon)) =G= sum( mth$(ord(mth) le ord(mon)) ,x(mth))
This is the equation right now, but (on the right side) I actually don’t need the sum from mth=1,…,mth=mon but instead I need the sum from the mon where y was equal to 1 for the last time until mth=mon, if that makes sense. Is this possible?
So let’s say we have
y(1)=0, y(2)=1, y(3)=0, y(4)=1, y(5)=0
I would need the following sum to be in the equation
… =G= x(1)+x(2)
… =G= x(3)+x(4)
… =G= x(5)
Obviously the equations would change with the y(mon).
Thanks a lot in advance!